Pembekalan Keterampilan Tata Rias Dan Rajutan Bagi Warga Binaan Sebagai Upaya Bela Negara Melalui Kemandirian Ekonomi Di Rutan Perempuan Kelas II A Surabaya - Megawati, Suci; Huda, Anam Miftakhul; Wahyuni, Jauhar; Setyowati, Raden Roro Nanik; Muzayanah, Muzayanah; Sari, Maya Mustika Kartika; Fitrie, Revienda Anita; Asmaranti, Anisa Dwi; Sajida, Rania Hanin; Shobirin, Dewi Rahma; Ana, Rani Rusdi; Ferina, Anggia Citra Okta (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
Inmates are not exempt from their fundamental human rights to meet the demands of life and livelihood, making it urgent to explore their potential and equip them with skills that can be developed after their release from prison as capital for starting a new life in society. Various skills training programs have been implemented by the prison and other institutions, but limited resources and the increasing number of inmates mean that these programs are still considered ineffective. The PKM team initiated a community service activity in the form of training on national defense through economic independence, followed by makeup and knitting craft training for female inmates at the Surabaya Class II A Women's Detention Center. The training was designed to be integrated and easy to understand, starting with an introduction to tools and materials, techniques and modifications in knitting stitches, up to the final product of the knitted items created. Similarly, for makeup, the training began with an introduction to the tools and materials required for facial makeup application, followed by techniques for applying makeup accurately. The methods used include mentoring, as well as pre-test and post-test assessments to measure participants' understanding levels. Data was collected through observation, questionnaires, interviews, and documentation. The results of this PKM initiative demonstrate an improvement in the inmates' understanding and skills in makeup application and knitting craftsmanship, fostering their enthusiasm for preparing for a more independent life after their sentence is completed.